Distribution of Zakat as a Solution Of Proverty Alleviation in Langsa City - Agustinar agustinar; Laila Mufida Laila Mufida; Siti Mu’allimah Siti Mu’allimah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
The focus of this research was the implementation of distribution of zakat as a solution of poverty alleviation in Langsa City. The problem in this research was, first, how was the concept of distribution in the Islamic Economic System? Second, how was the implementation of distribution of zakat in the Islamic Economic System in alleviating poverty? The purpose of this research was to describe the concept of distribution in the Islamic Economic System, and to analyze the implementation of distribution of zakat in the Islamic Economic System in alleviating poverty. The type of this research was a qualitative research by using descriptive analysis. It was a field research. The objects of this research were the poor people in Langsa City and the Baitul Mal Langsa. Based on the results and the analysis of discussion, it can be concluded that zakat had been distributed evenly. Therefore, zakat in Langsa City should be distributed with a larger budget and a wider scope, so that the benefits desired by Islam can be achieved and Langsa becomes one of the cities of baldatun thayyibatun wa rabbun ghafur in this beloved country of Indonesia.